The Effect Of Work Motivation On Employee Performance With Job Satisfaction As A Mediating Variable - Robi Nopandi; Nova Mardiana (International Journal of Economics, Business and Innovation Research, 2026)
Human resources play a strategic role in the hospitality industry because service quality is largely determined by employee performance. Three-star hotels in Bandar Lampung face intense competition, fluctuations in occupancy rates, and high service demands, making it important to improve employee performance. One factor that influences employee performance is work motivation, but high motivation does not necessarily result in optimal performance without the support of job satisfaction. Therefore, job satisfaction is seen as a variable that mediates the influence of work motivation on employee performance.This study uses a quantitative approach with purposive sampling techniques for employees of 3-star hotels in Bandar Lampung. Data collection was conducted by distributing questionnaires to 114 respondents who met the research criteria. The data obtained was then analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with the help of SmartPLS 4.0 software.The results of this study indicate that it supports the proposed hypothesis, namely that work motivation has a positive and significant effect on employee performance at 3-star hotels in Bandar Lampung. Furthermore, job satisfaction was found to mediate the relationship between work motivation and employee performance at 3-star hotels in Bandar Lampung. These findings imply that hotel management needs to improve working conditions, increase job satisfaction through fair systems, and strengthen training and interpersonal skills in order to encourage optimal employee performance.